Usability Evaluation of The Cinemas Indonesia CGV Application Using Heuristic Evaluation and Pieces Framework - Kusuma Ningrum, Linda Ayu; Fathoni, M Yoka; Setyodewi, RR Hutanti (Sistemasi: Jurnal Sistem Informasi, 2023)
The CGV Cinemas Indonesia application is an application that offers services for buying cinema tickets online. Even though the release of the CGV Cinemas Indonesia application was earlier than other cinema e-ticketing applications, this application actually has the lowest demand, judging from the application rating scale and the total number of downloads. Overall service quality can affect how satisfied users are. This study was conducted to evaluate the usability and service quality of the CGV Cinemas Indonesia application on user satisfaction using two related methods, namely the Heuristic Evaluation and Pieces Framework methods. Heuristic Evaluation is used to measure the extent of problems with the application's user interface. Pieces Framework is used to measure user satisfaction with application service quality. Where it is hoped that this research will produce recommendations for evaluating improvements related to CGV Cinemas Indonesia application problems. Based on the calculation results with the Heuristic Evaluation method, the average usability level is 67%. This percentage shows that the system has a good usability level. However, there are also several indicators that have a lower value than the minimum good system limit and need to be evaluated for improvement. In the results of calculations with the Pieces Framework, the final average satisfaction level is 3.5605; where in this case it can be concluded that the level of user satisfaction of the CGV Cinemas Indonesia application is included in the PUAS category. However, in terms of service quality, there are still several indicators on one dimension that need to be considered in the evaluation of improvements by application developers.